Dampak Orkestrasi Sumber Daya, Pertukaran Informasi Strategis, dan Orientasi Digital terhadap Inovasi dan Efisiensi Operasional dalam Rantai Pasokan Hotel - Sianipar, Ardin; Susanto, Roy Anthonius; Hasibuan, Jasman Saripuddin (Syntax Literate, 2025)
The hospitality industry faces increasingly complex challenges in supply chain management to achieve operational efficiency and sustainable innovation. This study aims to analyze the impact of resource orchestration, strategic information exchange, digital orientation on innovation and operational efficiency in the hotel supply chain. This study uses a literature review method to collect and analyze information from various relevant sources. The data collection technique in this study is a literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The results of the study show that resource orchestration, strategic information exchange, and digital orientation have a significant impact on innovation and operational efficiency in the hotel supply chain in Bandung. These three factors play an important role in improving the hotel's ability to innovate and run operations more efficiently.